Preparation, structured deliberate practice and decision making in elite level football: The case study of Gary Neville (Manchester United FC and England) - Horrocks, D. E.; McKenna, J.; Whitehead, A. E.; Taylor, P. J.; Morley, A. M.; Lawrence, I. (International Journal of Sports Science & Coaching, 2016)
Decision making in elite level sporting competition is often regarded as distinguishing success from failure. As an intricate brain-based process it is unlike other physical processes because it is invisible and is typically only evidenced after the event. This case study shows how an individual achieved great success in elite level professional football through consistent positive decision making on and off the field of play. Through prolonged interviewing, Gary Neville, a player from Manchester United Football Club, explored personal behaviours, the structure and activities of deliberate practice and his professional choices in match preparation. His career-long devotion to purposeful organised practice was focused on cognition, physical preparation, context-relative physical action and refined repetition to optimise his mental comfort while enhancing his match day performances. This approach was underpinned by diligent personal and collective organisation and by concerted action. Results provide an insight into the categorical nature of his deliberate practice, sport-specific information processing and match-based decision making. At the operational level, his process was mediated by a complex mental representation of ongoing and anticipated game situations; these representations were continuously updated during each match. Allowing for the limitations of the design, implications are provided for developmental and educational coaching, match preparation, deliberate practice activity and improved use of the performance analysis software packages in professional football. ABSTRACT FROM AUTHOR